THE EFFECT OF RIDDLE ON TEACHING VOCABULARY OF THE SEVENTH YEAR STUDENTS OF MTS NEGERI STABAT - Yusrah (Jurnal Sintaksis, 2019)
This study was purposed to find out the effect of riddle on teaching the vocabulary of the seventh -year students of MTs Negeri Stabat. The design of the study was experimental research. The population of this study was the seventh year students of MTs Negeri Stabat. There are six classes of the seventh year students consisting of 200 students. Since the population is large, the writer will take 70 students into her sample, namely two classes. To know the difference between the groups, the researchers used a comparative analysis technique between two groups which compared the means by applying the t-test formula. The observed data using t-test was 2.73 for the degree of freedom 68 (n1 + n2 – 2 = 35 + 35 – 2 = 68). In the row of 68 of the t-table was 1.671  = 0.05. The result showed that the t-observed was lower than the t-table, namely 2.73 < 1.671. Therefore, Riddles affects the Vocabulary achievement of the seventh- year students of MTs Negeri Stabat.